Design Principles Governing the Development of Theranostic Anticancer Agents and Their Nanoformulations with Photoacoustic Properties - Stavroula G. Kyrkou; Eirinaios I. Vrettos; Dimitris Gorpas; Timothy Crook; Nelofer Syed; Andreas G. Tzakos (MDPI AG, 2022)
The unmet need to develop novel approaches for cancer diagnosis and treatment has led to the evolution of theranostic agents, which usually include, in addition to the anticancer drug, an imaging agent based mostly on fluorescent agents. Over the past few years, a non-invasive photoacoustic imaging modality has been effectively integrated into theranostic agents. Herein, we shed light on the design principles governing the development of theranostic agents with photoacoustic properties, which can be formulated into nanocarriers to enhance their potency. Specifically, we provide an extensive analysis of their individual constituents including the imaging dyes, drugs, linkers, targeting moieties, and their formulation into nanocarriers. Along these lines, we present numerous relevant paradigms. Finally, we discuss the clinical relevance of the specific strategy, as also the limitations and future perspectives, and through this review, we envisage paving the way for the development of theranostic agents endowed with photoacoustic properties as effective anticancer medicines.